Upgrading fatigue - De Benedetto, Francesco (Medicina e Morale, 2024)
There are two positions that are difficult to reconcile and compose when it comes to the problem of professional updating: on the one hand, there is the unavoidable need for doctors to consolidate and refine their cultural and technical preparation, acquiring at least the most substantial and most easily transferable part of the knowledge deriving from a progress that never ceases to amaze: on the other hand, the overbearing and wearisome fatigue of a hard daily work commitment makes its harassing presence felt, which does not allow for any breaks and which does not allow room not only for study but also for the same family relationships or for some marginal Iudic activity.